1989
DOI: 10.1177/000456328902600501
|View full text |Cite
|
Sign up to set email alerts
|

New Cancer Markers

Abstract: In recent years many new and improved cancer markers have become available. From a clinical point of view, the most useful of the new markers include CA 19-9 for pancreatic adenocarcinoma, CA 125 for epithelial ovarian cancer, CA 15-3 for breast cancer, prostate specific antigen for prostatic adenocarcinoma, placental alkaline phosphatase for testicular seminomas and neuron-specific enolase for small cell carcinoma of lung. None of these new markers are specific for cancer. Furthermore, none are organ specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Longitudinal studies of healthy woman have demonstrated the statistical significance of this marker to monitor breast cancer patients (3). Several studies show that cancer markers often detect metastasis before a clinical manifestation (5,6). It has been determined that a number of tumor markers are present in saliva therefore its use as a diagnostic fluid could have significant diagnostic and logistical advantages when compared to serum (1).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies of healthy woman have demonstrated the statistical significance of this marker to monitor breast cancer patients (3). Several studies show that cancer markers often detect metastasis before a clinical manifestation (5,6). It has been determined that a number of tumor markers are present in saliva therefore its use as a diagnostic fluid could have significant diagnostic and logistical advantages when compared to serum (1).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, there is a need for new diagnostic and predictive factors to be able to choose the correct therapy and also to limit the treatment load given to each patient. Several studies show that cancer markers often detect metastasis before a clinical manifestation [3,4]. Numerous reports show that the immunoassays CA 15-3 and CEA are useful for breast cancer patients [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The most recently discovered breast cancer antigen is CA 15-3, which has been identified by reaction with two monoclonal antibodies (4). In clinical studies (5-7), it was found to detcct breast carcinoma metastases with higher sensitivity than the most widely used marker carcinoembryonic antigen (CEA).…”
mentioning
confidence: 99%